Лексические «дивергенция» и «конвергенция» между балтийскими и славянскими языками: статистический анализ материалов словаря Р. Траутмана - Inoue, Toshikazu (Baltistica, 1989)
LEXICAL “DIVERGENCE” AND “CONVERGENCE” BETWEEN BALTIC AND SLAVIC LANGUAGES: A STATISTIC ANALYSIS OF MATERIALS IN R. TRAUTMANN’S DICTIONARY As far as a clear answer has not been given with respect to the theory of “Balto-slavic linguistic unity”, apparent similarities in lexemes between these two linguistic groups should be examined in comparison with those among other linguistic groups. This paper is an attemp to show the “degrees” of similarities in the lexemes between Baltic and Slavic languages in a statistic manner. For this purpose, lexical materials are taken from R. Trautmann’s Dictionary (1923), and the analysis is based on two notions of “divergence” and “convergence”. On the basis of all the items in the Dictionary, the author of this paper distinguishes some groups of items in terms of their distributions. First, he draws a dividing line between the “convergence” type and the “divergence” type, the latter of which turns out to consist of three sub-types (D-1, D-2 and D-3). Then he regards the items of the “convergence” type as the “candidates” of the “Balto-Slavic lexemes” with the highest degree of commonness. The author finds in the Dictionary a group of 83 independent items on one hand, and a group of 10 derivative items on the other, which are both considered to belong to the “convergence” type. From the author’s point of view, other groups of items are, more or less, ranked in the peripheral position with respect to those “central” two groups of items.